Contribuições para o aprimoramento na utilização de andaimes suspensos em construções de edifícios conforme diretrizes da NR- 18 - Gomes, Alberto Roland (2006)
In this dissertation the subject of labor safety and health is approached, focusing on prevention of accidents when working in suspended scaffold, based on NR-18 as a preventive tool. The study initially presents information about Civil Engineering distributed in significant subjects for the intended targets is presented. In the second part details of suspended scaffold, pertinent guidelines of the NR-18 and no compulsory standards ABNT to be followed with this equipment are described. In the last part, the fulfillment of rules inserted in the NR-18, focused mainly to the suspended scaffold design, it is studied in the case study in a construction site. The conclusion shows the importance of the global view of the normative guidelines related to suspended scaffold, listed in this research, contributing for the complete fulfillment of the legal guidelines ans its improvement. The result achieved also might be useful as subsidies for the elaboration of the Conditions and Labor Environment Program for the Construction Industry, the project for the production of external covering, for the responsible organizations for monitoring of labor safety and health regulating standards